ICT Adoption in Micro and Small Firms: Can Internet Access Improve Labour Productivity? - Viollaz, Mariana (2018)
The rapid spread of information and communication technologies may increase firms’ productivity with important consequences for job creation and for economic growth. This article contributes to this discussion by analysing the impact of internet adoption on labour productivity and the mechanisms shaping this relationship in Peruvian micro and small manufacturing firms over the period 2011-2013. The article estimates a reduced form where labour productivity is a function of internet adoption and other explanatory factors. Internet adoption is instrumented using a measure of the availability of financial opportunities for micro and small firms in Peru. Findings indicate that internet adoption: (i) increases firms’ labour productivity; (ii) reallocates employment away from temporary administrative workers and non-remunerated workers and expands employment of permanent production workers; (iii) leads to the formalization of labour relationships, to the implementation of new organizational practices, and to the improvement of training measures. While changes in employment and formalization of workers are linked to labour productivity gains, increases in training measures and organizational changes do not generate any additional productivity increase.